The slow professor: challenging the culture of speed in the academy, by Maggie Berg and Barbara K. Seeber - Laasch, Oliver (Academy of Management, 2017)
This paper explores the principles of the Slow Movement to counter work-stress among university and college teachers. We believe that a Slow approach to teaching and learning may be the most effective way to counter the erosion of humanistic education by the corporate ethos of consumerism, efficiency, accountability, and standardisation We explore the principles of Slow not only to counter the consumer model of education but also to foster better teachers and learners. It is well-documented that changes in academic work have created significant stress among academic teachers (Catano, Francis, Haines, Kirpalani, Shannon, Stringer, & Lozanksi, 2007; Miller, Buckholdt & Shaw, 2008), and students (Dabney, 1995; Brown & Ralph 1999; Rowbotham and Julian 2006), but what requires further attention is the link between the corporate reliance on efficiency and the problem of lack of time in learning and teaching. Corporatisation has sped up the clock. The Slow Movement—originating in the Slow Food Movement—has gained recognition as a way to resist both globalization and the frantic pace of contemporary life. While slowness has been lauded in architecture, business, urban life and interpersonal relations, among others, it has yet to be applied to academia. Yet, if there is one sector of society that should be cultivating deep thought in themselves and others it is academic teachers. The consumerism that has taken hold in higher education propels the belief that time is money, resulting in superficial learning (Coté & Allahar, 2011b; Readings, 1996). Perhaps the most damaging effect of corporatisation in the universities is that individual educators feel paralysed in the face of overwhelming odds. Our focus on individuals and their own professional practice is conceived as political resistance to corporatisation.